Decreased Endothelial Nitric Oxide Bioavailability, Impaired Microvascular Function, and Increased Tissue Oxygen Consumption in Children with Falciparum Malaria - Yeo, Tsin W. (J Infect Dis, 2014)
Endothelial nitric oxide (NO) bioavailability, microvascular function, and host oxygen consumption have not been assessed in pediatric malaria. We measured NO-dependent endothelial function by using peripheral artery tonometry to determine the reactive hyperemia index (RHI), and microvascular function and oxygen consumption (VO(2)) using near infrared resonance spectroscopy in 13 Indonesian children with severe falciparum malaria and 15 with moderately severe falciparum malaria. Compared with 19 controls, children with severe malaria and those with moderately severe malaria had lower RHIs (P = .03); 12% and 8% lower microvascular function, respectively (P = .03); and 29% and 25% higher VO(2), respectively. RHIs correlated with microvascular function in all children with malaria (P < .001) and all with severe malaria (P < .001). Children with malaria have decreased endothelial and microvascular function and increased oxygen consumption, likely contributing to the pathogenesis of the disease.